THE EFFECT OF FAIR VALUE IMPLEMENTATION ON CASH FLOW FORECASTING (CASE STUDY: BANKING COMPANY LISTED IN INDONESIAN STOCK EXCHANGE YEAR 2014-2015) - Riesa Morita Yuliasari; Mukhtaruddin Mukhtaruddin; Tertiarto Wahyudi (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
This study has one main objectives; to investigate about the significant effect of fair value implementation in forecasting cash flow on Banking Company in Indonesia. The methodology used in this research is quantitative research, so the data are collected from secondary data by using purposive sampling technique of Banking Company’s Financial Statement uploaded in Indonesian Stock Exchange which related to this research. The number of sample in this research are 36 financial statement of Banking Company in Indonesia for year 2014 and 2015 consist of 18 financial statement that implement fair value and 18 financial statement that still implement historical cost. The results of this study show that the implementation of fair value does significantly influence cash flow forecasting of Banking Company in Indonesia.